In-situ formation agent, lithium symmetric battery, all-solid-state battery and preparation method of lithium symmetric battery and all-solid-state battery
By using in-situ chemical agents in all-solid-state batteries to form an electrochemically stable internal structure in situ, the problem of poor compatibility between solid electrolyte and negative electrode is solved, and long-term stable cycles of all-solid-state batteries and extended battery life are achieved.
Patent Information
- Application Number
- CN202411633776.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The poor compatibility of solid electrolytes and negative electrodes in all-solid-state batteries causes lithium dendrites to grow through the electrolytes, resulting in battery failure, and hindering the commercial application of all-solid-state batteries.
Provides an in-situ chemical agent with the chemical formula of LiaMbNcXd, which is prepared by ball milling, and can form an electrochemically stable internal structure in situ with the assistance of external conditions, including a three-dimensional porous frame and a multivariate composite interface, improving the compatibility of solid electrolytes and negative electrodes. sex.
Through the use of in-situ chemical agents, the long-term stable circulation performance of all-solid state batteries can be significantly improved, prevent lithium dendrites from penetrating the electrolyte, and prolonging battery life.
Smart Images

Figure CN119447529A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an in-situ formation agent, a lithium symmetric battery and an all-solid-state battery and a preparation method thereof. Background Art
[0002] With the development of society, the rapid development of electric vehicles and wearable devices has met the needs of human life and work, so there is a further demand for high-performance and high-safety batteries. However, currently commercial lithium-ion batteries generally use organic liquid electrolytes, including electrolyte lithium salts, organic solvents, and additives. In the application of traditional liquid ion batteries, the lithium metal negative electrode will not be able to inhibit the growth of lithium dendrites and pierce the battery separator. In addition, during the charging and discharging process of the battery, due to overcharging and other reasons, the electrolyte is consumed, the battery temperature rises, causing the battery to short-circuit and become flammable and explosive. Various safety issues have made researchers begin to pay attention to the development of solid electrolytes. By using non-flammable, high-mechanical modulus solid electrolytes (SSEs) instead of liquid electrolytes, all-solid-state batteries (ASSBs) can provide inherent safety advantages.
[0003] Among them, in 2018, Asano et al. prepared Li3YCl6 (LYC) (5.1 × 10 -4 S∙cm -1 ) and Li3YBr6 (LYB) (1.7 × 10 -3 S∙cm -1 ), since then, halide solid electrolytes have received widespread attention. Studies have shown that halide solid electrolytes have good mechanical rigidity, electrochemical oxidation stability, very high room temperature ionic conductivity and a wide electrochemical window. Wang et al. pointed out that the thermodynamic oxidation potential of solid electrolytes (SEs) containing chloride anion sublattices is usually 4.2V-4.3V, and the ionic conductivity is higher than 1 ms cm -1, has great application prospects, and can increase / decrease ionic conductivity by doping; sulfide and oxide solid electrolytes have also been studied for decades. Oxides have the characteristics of chemical stability, electrochemical oxidation stability, and high electrochemical oxidation voltage; sulfides have the characteristics of high ionic conductivity, good mechanical deformability, and low grain boundary resistance. In recent years, researchers have conducted a lot of research on electrode / electrolyte interfaces, solid electrolytes, lithium metal and its composite materials, silicon and its composite materials, and carbon and its composite negative electrodes. Although it has been reported that some solid electrolytes have good compatibility with some negative electrodes, there are still many problems that have not been overcome in all-solid-state batteries. For example, in sulfide solid-state electrolysis all-solid-state lithium metal batteries, as the battery cycles, lithium dendrites grow through Li6PS5Cl and cause it to fail. However, the growth of such lithium dendrites is unavoidable; in oxide solid-state electrolysis, similarly, Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The uncontrollable growth of lithium dendrites leads to battery failure, which hinders the commercial application of all-solid-state batteries. Summary of the invention
[0004] In order to solve the problem of poor compatibility between solid electrolyte and negative electrode in all-solid-state batteries, the present invention provides an in-situ formation agent, which, with the assistance of external conditions, can form an electrochemically stable internal structure in situ, improve the compatibility between the solid electrolyte and the negative electrode, and promote long-term stable circulation of the all-solid-state battery.
[0005] The present invention also provides a lithium symmetrical battery, an all-solid-state battery and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides an in-situ chemical forming agent, the chemical formula of the in-situ chemical forming agent is Li a M b N c X d ;
[0008] Wherein, M and N are each independently selected from at least one of Y, La, Ta, Zr, P, Ti, Hf and Al;
[0009] X is selected from at least one of F, Cl, Br, I, O and S;
[0010] a is 0~4; b is 0~4; c is 0~4; d is 3~12.
[0011] Based on the same inventive concept, the present invention provides a method for preparing an in-situ formation agent, the preparation method comprising:
[0012] Weigh the raw materials and place them in a ball mill for ball milling;
[0013] The conditions for the ball milling treatment include at least one of (1) to (4):
[0014] (1) The ball milling speed is 400rpm / min-600rpm / min;
[0015] (2) Ball milling time is 1h-4h;
[0016] (3) The ball milling medium is zirconia beads with a diameter of 3 mm to 10 mm;
[0017] (4) The mass ratio of the zirconium oxide beads to the raw material is (40-60):1;
[0018] The raw material includes at least one of YCl3, LaCl3, TaCl5, ZrCl4, HfCl, Li2O, Al2O3, TiO2, P2O5, LiA and Li2S;
[0019] In the LiA, A is selected from F, Cl, Br and I.
[0020] Based on the same inventive concept, the present invention provides an in-situ forming agent Li 2.2 LaI2O 0.1 A preparation method of Cl3, the preparation method comprising:
[0021] LiI, LaCl3, and Li2O were weighed in a zirconia ball mill according to a stoichiometric ratio of 2:1:0.1 and ball milled to obtain Li 2.2 LaI2O 0.1 Cl3 powder;
[0022] The conditions for ball milling include at least one of (1) to (4):
[0023] (1) The ball milling speed is 400rpm / min-600rpm / min;
[0024] (2) Ball milling time is 1h-4h;
[0025] (3) The ball milling medium is zirconia beads with a diameter of 3 mm to 10 mm;
[0026] (4) The ratio of zirconia ball milling beads to halide solid electrolyte material is (40-60):1.
[0027] Based on the same inventive concept, the present invention provides an in-situ forming agent Li 0.374 Ta 0.350 La 0.875A preparation method of Cl3, the preparation method comprising:
[0028] LiCl, LaCl3, and TaCl5 were weighed in a zirconia ball mill according to a stoichiometric ratio of 1.1:1:2.5 and milled to obtain Li 0.374 Ta 0.350 La 0.875 Cl3 powder;
[0029] The conditions for ball milling include at least one of (1) to (4):
[0030] (1) The ball milling speed is 400rpm / min-600rpm / min;
[0031] (2) Ball milling time is 1h-4h;
[0032] (3) The ball milling medium is zirconia beads with a diameter of 3 mm to 10 mm;
[0033] (4) The ratio of zirconia ball milling beads to halide solid electrolyte material is (40-60):1.
[0034] Based on the same inventive concept, the present invention provides a battery assembly based on an in-situ formation agent, wherein the battery assembly includes any one of a to e:
[0035] a. The in-situ chemical forming agent is prepared by a dry process into a 5-40μm thick dry film;
[0036] b. The in-situ chemical forming agent is prepared by a wet process into a 5-10 μm thick wet film;
[0037] c. The in-situ forming agent is mixed with a solid or semi-solid electrolyte and pressed into an electrolyte sheet with a thickness of 5-30 μm by a cold pressing process;
[0038] d. The in-situ chemical forming agent is formed into a 5-30 μm thick film on the surface of a solid or semi-solid electrolyte by vapor deposition technology or deposition-transfer technology;
[0039] e. The in-situ formation agent is cold pressed through a solid-state battery mold to form a 5-40 μm thick formation sacrificial layer.
[0040] Further, the battery assembly further includes a lithium metal negative electrode, the lithium metal negative electrode is in direct contact with any one of the dry film, the wet film, the electrolyte sheet, the film and the formation sacrificial layer;
[0041] The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and a composite of one or more of a PEO-based polymer.
[0042] Based on the same inventive concept, the present invention provides a lithium symmetric battery, the lithium symmetric battery comprising a lithium metal negative electrode, a solid or semi-solid electrolyte and the in-situ formation agent;
[0043] The assembly structure of the lithium symmetric battery is lithium metal negative electrode||in-situ formation agent||lithium metal negative electrode;
[0044] Alternatively, the assembly structure of the lithium symmetrical battery is lithium metal negative electrode||in-situ formation agent||solid or semi-solid electrolyte||in-situ formation agent||lithium metal negative electrode;
[0045] Wherein, the lithium metal negative electrode comprises a lithium metal sheet or a lithium foil;
[0046] The solid or semi-solid electrolyte includes a composite of one or more of a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte and a halide electrolyte.
[0047] Furthermore, the thickness of the lithium metal sheet is 4 mm, and the thickness of the lithium foil is 20 μm;
[0048] The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and a composite of one or more of a PEO-based polymer.
[0049] Furthermore, in the lithium symmetrical battery, the thickness of the solid or semi-solid electrolyte is 0.005 to 0.04 mm, and the thickness of the in-situ formation agent is 0.005 to 0.04 mm.
[0050] Furthermore, the lithium symmetric battery is prepared by the following method:
[0051] Assembling the lithium metal and the in-situ forming agent according to the structure of lithium metal||in-situ forming agent||lithium metal to obtain an assembly I;
[0052] Alternatively, the lithium metal, the in-situ forming agent and the solid or semi-solid electrolyte are assembled according to the structure of lithium metal||in-situ forming agent||solid or semi-solid electrolyte||in-situ forming agent||lithium metal to obtain an assembly II;
[0053] The assembly I or the assembly II is left standing for 24 - 60 h under the assistance of external conditions to obtain the lithium symmetric battery;
[0054] Among them, the external condition assistance includes at least one of external pressure assistance, temperature assistance, and electrochemical charge-discharge cycle assistance.
[0055] Further, in the external pressure assistance, the external pressure is 0.1 MPa - 50 Mpa;
[0056] In the temperature assistance, the temperature is -30 - 90 °C;
[0057] In the electrochemical charge-discharge cycle assistance, the electrochemical charge-discharge cycle is a current of 0.01 - 0.1 C.
[0058] Based on the same inventive concept, the present invention provides a all-solid-state battery, which includes a solid or semi-solid electrolyte, a negative electrode sheet, a composite positive electrode, and the in-situ forming agent;
[0059] The solid or semi-solid electrolyte includes a composite of one or more of Li6PS5Cl, Li 6.4 La3Zr 1.4 Ta 0.6 O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6, and PEO-based polymers;
[0060] The preparation raw materials of the negative electrode sheet include at least one of lithium metal, lithium-containing compounds, silicon, silicon-containing compounds, carbon, and carbon-containing compounds; the composite positive electrode is prepared by uniformly mixing an electrolyte material, a positive electrode active material, and a conductive carbon material in a mass ratio of (30% - 50%):(70% - 50%):1%;
[0061] Among them, the electrolyte material includes the in-situ forming agent or the solid or semi-solid electrolyte.
[0062] Further, the positive electrode active material includes at least one of CF a , sulfur, sulfur-containing compounds, lithium iron phosphate, lithium-rich positive electrode material, LiCoO2, and LiNi x Co y Mn 1-x-y O2, where 0.5 < a < 1.3, 0 < x < 1, 0 < y < 1, and x + y < 1;
[0063] The thickness of the solid or semi-solid electrolyte is 0.03 - 0.04 mm, the thickness of the negative electrode sheet is 0.02 - 4 mm, the thickness of the composite positive electrode is 0.01 - 0.02 mm, and the thickness of the in-situ forming agent is 0.005 - 0.04 mm.
[0064] Based on the same inventive concept, the present invention provides an in-situ formation agent for a sodium ion battery, wherein the chemical formula of the in-situ formation agent for a sodium ion battery is Na a M b N c X d ;
[0065] Wherein, M and N are each independently selected from at least one of Y, La, Ta, Zr, P, Ti, Hf and Al;
[0066] X is selected from at least one of F, Cl, Br, I, O and S;
[0067] a is 0~4; b is 0~4; c is 0~4; d is 3~12.
[0068] Based on the same inventive concept, the present invention provides an application of an in-situ formation agent for a sodium ion battery in the preparation of a sodium symmetric battery or a sodium all-solid-state battery.
[0069] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0070] 1. The present invention discloses an in-situ formation agent, which can form an electrochemically stable internal structure in situ in an all-solid-state battery with the assistance of external conditions. The internal structure comprises a three-dimensional porous framework and a multi-component composite interface, which can make the solid electrolyte compatible with the negative electrode, thereby achieving the purpose of long-term stable circulation of the all-solid-state battery.
[0071] 2. The present invention provides a lithium symmetrical battery, which forms an electrochemically stable internal structure in situ at the interface between the electrolyte and the negative electrode by assisting an in-situ formation agent under external conditions such as external pressure and standing for 3-80 hours, wherein the stable internal structure comprises a three-dimensional porous framework and a multi-component composite interface, which enables the solid electrolyte to be compatible with the negative electrode, thereby achieving the purpose of long-term stable circulation of the lithium symmetrical battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0073] Figure 1 A cycle diagram of a Li||SSE||Li lithium symmetric battery of the present invention;
[0074] Figure 2This is a full battery cycle diagram prepared based on the in-situ formation agent of the present invention;
[0075] Figure 3 This is a CT image of a lithium symmetric battery prepared based on an in-situ formation agent according to the present invention;
[0076] Figure 4 This is a full battery cycle diagram prepared based on the in-situ formation agent of the present invention;
[0077] Figure 5 This is a cycle diagram of a lithium symmetric battery without an in-situ formation agent according to the present invention.
[0078] Figure 6 This is a cycle diagram of the all-solid-state battery without an in-situ formation agent of the present invention.
[0079] Figure 7 This is the XPS graph of SSE and original SSE powder after cycling in a Li||SSE||Li lithium symmetric battery of the present invention. DETAILED DESCRIPTION
[0080] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0081] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0082] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0083] The technical principle of the present invention is as follows:
[0084] The present invention provides an in-situ chemical forming agent, wherein the chemical formula of the in-situ chemical forming agent is Li a M b N c X d ;
[0085] Wherein, M and N are each independently selected from at least one of Y, La, Ta, Zr, P, Ti, Hf and Al;
[0086] X is selected from at least one of F, Cl, Br, I, O and S;
[0087] a is 0~4; b is 0~4; c is 0~4; d is 3~12.
[0088] The present invention provides a battery assembly of an in-situ formation agent, wherein the battery assembly comprises any one of a to e:
[0089] a. The in-situ chemical forming agent is prepared by a dry process into a 5-40μm thick dry film;
[0090] b. The in-situ chemical forming agent is prepared by a wet process into a 5-10 μm thick wet film;
[0091] c. The in-situ forming agent is mixed with a solid or semi-solid electrolyte and pressed into an electrolyte sheet with a thickness of 5-30 μm by a cold pressing process;
[0092] d. The in-situ chemical forming agent is formed into a 5-30 μm thick film on the surface of a solid or semi-solid electrolyte by vapor deposition technology or deposition-transfer technology;
[0093] e. The in-situ formation agent is cold pressed through a solid-state battery mold to form a 5-40 μm thick formation sacrificial layer.
[0094] In the present invention, the practical uses of the battery components a to e include: they can be used as a sacrificial layer that reacts with lithium metal to achieve stable circulation of halide solid electrolyte all-solid-state lithium metal batteries; they are used as protective layers for sulfide solid electrolyte and oxide solid electrolyte lithium metal batteries to prevent lithium dendrites from penetrating the electrolyte and causing battery failure.
[0095] The present invention provides a lithium symmetrical battery, which comprises a lithium metal negative electrode, a solid or semi-solid electrolyte and the in-situ formation agent;
[0096] The assembly structure of the lithium symmetric battery is lithium metal negative electrode||in-situ formation agent||lithium metal negative electrode;
[0097] Alternatively, the assembly structure of the lithium symmetrical battery is lithium metal negative electrode||in-situ formation agent||solid or semi-solid electrolyte||in-situ formation agent||lithium metal negative electrode;
[0098] Wherein, the lithium metal negative electrode comprises a lithium metal sheet or a lithium foil;
[0099] The solid or semi-solid electrolyte includes a composite of one or more of a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte and a halide electrolyte.
[0100] Preferably, the thickness of the lithium metal sheet is 4 mm, and the thickness of the lithium foil is 20 μm;
[0101] The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 Ln3Z 1.4 Ta 0.6O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and a composite of one or more of a PEO-based polymer.
[0102] In the present invention, the solid or semi-solid electrolyte is but not limited to Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and PEO-based polymers have the following advantages: Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O 12 , the growth of lithium dendrites causes the failure of this type of lithium metal symmetric battery. The use of an in-situ formation agent can prevent lithium dendrites from penetrating these two types of electrolytes, making the lithium symmetric battery / full battery cycle time longer and improving the battery life; LiAlOCl4, LiNbOCl4, Li3InCl6 and lithium metal react violently, especially Li3InCl6. The in-situ formation agent can prevent the reaction of the violently reactive halide solid electrolyte with lithium metal, making the lithium symmetric battery / full battery cycle time longer.
[0103] Furthermore, the lithium symmetric battery is prepared by the following method:
[0104] Assembling the lithium metal and the in-situ forming agent according to the structure of lithium metal||in-situ forming agent||lithium metal to obtain an assembly I;
[0105] Alternatively, the lithium metal, the in-situ forming agent and the solid or semi-solid electrolyte are assembled according to the structure of lithium metal||in-situ forming agent||solid or semi-solid electrolyte||in-situ forming agent||lithium metal to obtain an assembly II;
[0106] The assembly I or the assembly II is allowed to stand for 24-60 hours under external conditions to obtain the lithium symmetrical battery;
[0107] Wherein, the external condition assistance includes at least one of external pressure assistance, temperature assistance and electrochemical charge and discharge cycle assistance.
[0108] Preferably, in the external pressure assistance, the external pressure is 0.1 MPa to 50 MPa;
[0109] In the temperature assistance, the temperature is -30 to 90°C;
[0110] In the electrochemical charge and discharge cycle assistance, the electrochemical charge and discharge cycle is 0.01 to 0.1 C current.
[0111] Optionally, the present invention further provides a method for preparing an all-solid-state battery, which specifically comprises:
[0112] Step 1: In a glove box protected by an argon atmosphere (H2O<0.01ppm, O2<0.01ppm), the in-situ formation agent material, the positive electrode active material and the conductive carbon material are mixed in a mass ratio of (30%-50%):(70%-50%):1%, and ground with an agate mortar for 20 minutes to mix the two as fully as possible, thereby obtaining a composite positive electrode powder;
[0113] Step 2: The negative electrode material uses commercially purchased lithium metal and its alloy materials, silicon and its composite materials, carbon and its composite materials; nano silicon and commercial metal lithium powder are mixed in a certain proportion, put into a ball mill at a speed of 200 rpm / min for 2 hours, and the ball milling medium is zirconium oxide ball milling beads with a diameter of 3mm-10mm, so as to obtain a lithium silicon negative electrode;
[0114] Step 3,
[0115] (1) The in-situ forming agent and PTFE are mixed evenly in a mass ratio of (98%-99%): (2%-1%), and then rolled on a heating table to prepare a 5-40 μm dry film, which is then cut into a dry film with a diameter of 10 mm;
[0116] (2) Stir the in-situ forming agent and n-hexane into a uniform slurry in a container, use a coating machine to prepare a wet film of 5-10 μm, and cut it into a wet film with a diameter of 10 mm after complete drying;
[0117] (3) Mix the in-situ formation agent and the solid / semi-solid electrolyte in a ratio of 1:1 and grind them in an agate mortar for 20 min to mix them as evenly as possible;
[0118] (4) Forming a 5-10 μm thin film on the surface of a pressed solid / semi-solid electrolyte by vapor deposition or deposition-transfer technology;
[0119] (5) The in-situ formation agent and the lithium (alloy) negative electrode are mixed in a certain proportion, and ground in an agate mortar for 20 minutes to make the two mixed as evenly as possible to obtain a mixed negative electrode;
[0120] Step 4: All-solid-state battery assembly:
[0121] In a solid-state battery mold with a diameter of 10 mm, the solid / semi-solid electrolyte and the composite positive electrode obtained in step 1 are pressed in sequence, the (1) dry film obtained in step 3 is stacked on the lower end of the solid / semi-solid electrolyte, cold pressed, and finally the negative electrode material is pressed to obtain a complete all-solid-state battery;
[0122] In a solid-state battery mold with a diameter of 10 mm, the solid / semi-solid electrolyte and the composite positive electrode obtained in step 1 are pressed in sequence, the (2) wet film obtained in step 3 is transferred to the lower end of the solid / semi-solid electrolyte, cold pressed, and finally the negative electrode material is pressed to obtain a complete all-solid-state battery;
[0123] In a solid-state battery mold with a diameter of 10 mm, the mixed material of step three (3), the composite positive electrode obtained in step one, and finally the negative electrode material are pressed in sequence to obtain a complete all-solid-state battery;
[0124] The solid / semi-solid electrolyte sheet obtained in step 3 (4) is transferred to a solid-state battery mold with a diameter of 10 mm, and the composite material obtained in step 1 is pressed on the upper end of the solid / semi-solid electrolyte sheet, and finally the negative electrode material is pressed to obtain a complete all-solid-state battery;
[0125] In a solid-state battery mold with a diameter of 10 mm, the solid / semi-solid electrolyte, the composite positive electrode obtained in step 1, and the mixed negative electrode obtained in step 3 (5) are pressed in sequence to obtain a complete all-solid-state battery;
[0126] Symmetrical battery assembly: replace the composite positive electrode in the all-solid-state battery assembly process with the same material as the corresponding negative electrode;
[0127] Step 5: The full battery and symmetrical battery obtained above are allowed to stand for 24-60 hours, and in-situ formation is assisted under two or three conditions: an external pressure of 0.1 MPa to 50 MPa, a temperature of -30 to 90 degrees Celsius, and an electrochemical charge and discharge cycle of 0.01 to 0.1C current.
[0128] The following will describe in detail an in-situ formation agent, a lithium symmetric battery, an all-solid-state battery and a preparation method thereof in combination with embodiments and experimental data.
[0129] Example 1
[0130] This embodiment prepares a lithium symmetrical battery and an all-solid-state battery, as follows:
[0131] 1. In a glove box protected by argon atmosphere (H2O<0.01ppm, O2<0.01ppm), LiCl, LaCl3, and TaCl5 were weighed in a zirconia ball mill according to the stoichiometric ratio of 1.1:1:2.5, and Li was synthesized by ball milling at 600rpm / min for 3h. 0.374 Ta 0.350 La 0.875 Cl3 white powder, wherein the ball milling medium is zirconia beads with a diameter of 3mm-10mm; the ratio of zirconia ball milling beads to halide solid electrolyte material is 60:1, Li 0.374 Ta 0.350 La0.875 Cl3 is used as both an in-situ formation agent and an electrolyte. 100-150 mg of in-situ formation agent powder is weighed and placed in a 10 mm diameter stainless steel solid-state battery mold, and cold pressed at 200 MPa to form an in-situ formation agent sheet with a thickness of 0.46-0.5 mm. Lithium metal sheets with a diameter of 10 mm and a thickness of 4 mm are placed on the upper and lower ends of the electrolyte and pressed at a pressure of 5 MPa to obtain an assembly I with a lithium metal||in-situ formation agent||lithium metal (Li||SSE||Li) structure.
[0132] 2. The above assembly I was tested in a blue battery test system. The experimental assembly I was subjected to an external pressure of 5 MPa and allowed to stand for 60 hours. The comparative experimental lithium symmetric battery was allowed to stand for 6 hours. The test process was carried out at 0.2 mA cm -2 The lithium deposition / stripping test was carried out at room temperature with a current density of Figure 1 As shown, the cycle stability is analyzed. It can be seen that the comparative experimental lithium symmetric battery is left to stand for 6 hours. As the cycle time increases, the overvoltage / polarization voltage gradually increases. When the cycle reaches 600 hours, the overvoltage / polarization voltage reaches 0.9V, which cannot be stably cycled for a long time; on the contrary, the experimental lithium symmetric battery is left to stand for 60 hours and under the action of an external pressure of 5MPa, the overvoltage / polarization voltage is only about 0.3V in the initial cycle. As the cycle time increases, the overvoltage / polarization voltage slowly decreases and reaches a more stable state, indicating that the in-situ formation agent enables the lithium symmetric battery to achieve the purpose of long-term stable cycle after the in-situ formation process of external pressure and standing for 60 hours.
[0133] 3. Assembly of all-solid-state lithium metal batteries: In a glove box protected by argon atmosphere (H2O<0.01ppm, O2<0.01ppm), Li 0.374 Ta 0.350 La 0.875 Cl3 powder (can be used as an in-situ formation agent or electrolyte): LiCoO2: acetylene black are prepared in a mass ratio of 30:70:1. These materials are mixed in an agate mortar to obtain a composite positive electrode powder. 0.374 Ta 0.350 La 0.875 Cl3 powder was pressed into a sheet at 200 MPa (which can be used as a sacrificial layer or directly as an electrolyte). Then 6-8 mg of the composite positive electrode powder was weighed and placed on the Li 0.374 Ta 0.350 La 0.875Cl3 sheet, 360MPa pressure is applied to laminate the positive electrode and electrolyte together, and finally a lithium sheet with a diameter of 10mm and a thickness of 4mm is laminated on the negative terminal (lower end) to obtain a laminate, and an equivalent pressure of 5MPa is applied to the laminate to make the laminate tightly bonded, and then sealed and left to stand for 24 hours before testing in the blue battery test system. After standing for 24 hours, the charge / discharge cycle is carried out at 0.1C. The test results are as follows Figure 2 As shown. 0.374 Ta 0.350 La 0.875 When Cl3 and lithium metal are assembled into a full battery, they can 0.374 Ta 0.350 La 0.875 A stable three-dimensional porous framework and multi-component composite interface are formed in situ at the interface between Cl3 and lithium metal, which protects the electrolyte and thus achieves a stable circulation effect.
[0134] 4. Characterization of lithium symmetric battery: Select part of the electrolyte (i.e., SSE part) of the experimental lithium symmetric battery that was left to stand for 60 h in step 2 for CT testing (e.g. Figure 3 ). Since the in-situ formation agent forms a three-dimensional porous framework structure during in-situ formation, pores are used to represent the interface state after in-situ formation. This sample was taken after a lithium symmetric battery was left to cycle for 60 hours. Part of sample 1 (SSE part) was taken out from the symmetric battery for analysis. The in-situ formation part 2 photographed by CT can be seen. The gray part is the pores. The stronger the continuity of the gray part, the more pores there are. Opening slice 3, it can be seen that the pores at the upper end in contact with the lithium metal are larger, but the porous structure formed in situ is uniform (dashed part). There are some smaller pores at the lower end, which are the inherent gaps between particles formed by the in-situ formation agent during the cold pressing process. Obviously, there is a lot of interfacial friction between the lithium metal and the in-situ formation agent Li 0.374 Ta 0.350 La 0.875 After 60 hours of static and external pressure, Cl3 formed a stable internal structure in situ, namely a three-dimensional porous structure, and after XPS testing (the results are shown in Figure 7 ) It can be found that this is a multi-component composite interface layer, Li 0.374 Ta 0.350 La 0.875 The interface product of Cl3 after the cycle is Ta x O y , La 0 ,LiCl,It is this structure that enables all-solid-state batteries and lithium symmetric batteries to cycle stably.
[0135] Example 2
[0136] In a glove box protected by argon atmosphere (H2O < 0.01ppm, O2 < 0.01ppm), LiI, LaCl3, and Li2O were weighed in a zirconia ball mill according to a stoichiometric ratio of 2:1:0.1, and Li was synthesized by ball milling at a speed of 600 rpm / min for 4 h. 2.2 LaI2O 0.1 Cl3 white powder, the ball milling medium is zirconia beads with a diameter of 3mm-10mm; the ratio of zirconia ball milling beads to halide solid electrolyte material is 50:1, Li 2.2 LaI2O 0.1 Cl3 was used as both an in-situ formation agent and an electrolyte to prepare Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2@Li6PS5Cl composite cathode (Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2, Li6PS5Cl, and acetylene black were mixed in a mass ratio of 70:30:1), and the same method for preparing all-solid-state batteries as in Example 1 was used to assemble Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2@Li6PS5Cl|| Li6PS5Cl|| Li 2.2 LaI2O 0.1 The Cl3||Li all-solid-state battery was charged / discharged at 0.1C after standing for 24 hours. The test results are as follows: Figure 4 As shown in the figure, the all-solid-state battery after in-situ formation shows good cycle performance. (In the figure, NCM90 represents Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2@Li6PS5Cl)
[0137] Comparative Example 1
[0138] The composite positive electrode preparation method of Example 1 was used to prepare Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2@Li6PS5Cl composite positive electrode, the same method for preparing all-solid-state batteries as in Example 1 was used to assemble Li[Ni 0.90 Co 0.05 Mn 0.05 ]O2@Li6PS5Cl|| Li6PS5Cl|||Li all-solid-state battery, charge / discharge cycle at 0.1C, the test results are as follows Figure 5 As shown in the figure, the all-solid-state battery can be charged and discharged normally in the first cycle, and the first cycle discharge capacity reaches 186.7 mAh g-1 ,However, in the absence of an in-situ formation agent, an obvious voltage drop occurs in the second cycle, which is the short-circuit behavior of the full battery.
[0139] Comparative Example 2
[0140] Synthesis of Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The solid electrolyte sheet was used to assemble a lithium symmetric battery. The assembly method was the same as that of the lithium symmetric battery in Example 1 (no external pressure, only standing for 6 hours). The results were as follows: Figure 6 As shown, without in-situ formation and in-situ formation agent, the lithium symmetric battery experienced an overvoltage drop, i.e. a short circuit, in less than 300 hours of cycling.
[0141] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0142] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0143] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. An in-situ formation agent, characterized in that: The chemical formula of the in-situ formation agent is Li a M b N c X d ; Wherein, M and N are each independently selected from at least one of Y, La, Ta, Zr, P, Ti, Hf and Al; X is selected from at least one of F, Cl, Br, I, O and S; a is 0~4; b is 0~4; c is 0~4; d is 3~12.
2. The method for preparing an in-situ formation agent according to claim 1, characterized in that: The preparation method comprises: Weigh the raw materials and place them in a ball mill for ball milling; The conditions for the ball milling treatment include at least one of (1) to (4): (1) The ball milling speed is 400rpm / min-600rpm / min; (2) Ball milling time is 1h-4h; (3) The ball milling medium is zirconia beads with a diameter of 3 mm to 10 mm; (4) The mass ratio of the zirconium oxide beads to the raw material is (40-60):1; The raw material includes at least one of YCl3, LaCl3, TaCl5, ZrCl4, HfCl, Li2O, Al2O3, TiO2, P2O5, LiA and Li2S; In the LiA, A is selected from F, Cl, Br and I.
3. A battery assembly based on an in-situ formation agent according to claim 1, characterized in that: The battery assembly includes any one of a to e: a. The in-situ chemical forming agent is prepared by a dry process into a 5-40μm thick dry film; b. The in-situ chemical forming agent is prepared by a wet process into a 5-10 μm thick wet film; c. The in-situ forming agent is mixed with a solid or semi-solid electrolyte and pressed into an electrolyte sheet with a thickness of 5-30 μm by a cold pressing process; d. The in-situ chemical forming agent is formed into a 5-30 μm thick film on the surface of a solid or semi-solid electrolyte by vapor deposition technology or deposition-transfer technology; e. The in-situ formation agent is cold pressed through a solid-state battery mold to form a 5-40 μm thick formation sacrificial layer.
4. The battery assembly based on an in-situ formation agent according to claim 3, characterized in that: The battery assembly further includes a lithium metal negative electrode, the lithium metal negative electrode being in direct contact with any one of the dry film, the wet film, the electrolyte sheet, the film and the formation sacrificial layer; The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and a composite of one or more of a PEO-based polymer.
5. A lithium symmetrical battery, characterized in that: The lithium symmetric battery comprises a lithium metal negative electrode, a solid or semi-solid electrolyte and the in-situ formation agent according to claim 1; The assembly structure of the lithium symmetric battery is lithium metal negative electrode||in-situ formation agent||lithium metal negative electrode; Alternatively, the assembly structure of the lithium symmetrical battery is lithium metal negative electrode||in-situ formation agent||solid or semi-solid electrolyte||in-situ formation agent||lithium metal negative electrode; Wherein, the lithium metal negative electrode comprises a lithium metal sheet or a lithium foil; The solid or semi-solid electrolyte includes a composite of one or more of a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte and a halide electrolyte.
6. A lithium symmetrical battery according to claim 5, characterized in that: The thickness of the lithium metal sheet is 4 mm, and the thickness of the lithium foil is 20 μm; The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , LiAlOCl4, LiNbOCl4, Li3InCl6 and a composite of one or more of a PEO-based polymer.
7. A lithium symmetrical battery according to claim 5, characterized in that: In the lithium symmetrical battery, the thickness of the solid or semi-solid electrolyte is 0.005-0.04 mm, and the thickness of the in-situ formation agent is 0.005-0.04 mm.
8. A lithium symmetrical battery according to any one of claims 5 to 7, characterized in that: The lithium symmetric battery is prepared by the following method: Assembling the lithium metal and the in-situ forming agent according to the structure of lithium metal||in-situ forming agent||lithium metal to obtain an assembly I; Alternatively, the lithium metal, the in-situ forming agent and the solid or semi-solid electrolyte are assembled according to the structure of lithium metal||in-situ forming agent||solid or semi-solid electrolyte||in-situ forming agent||lithium metal to obtain an assembly II; The assembly I or the assembly II is allowed to stand for 24-60 hours under external conditions to obtain the lithium symmetrical battery; Wherein, the external condition assistance includes at least one of external pressure assistance, temperature assistance and electrochemical charge and discharge cycle assistance.
9. A lithium symmetrical battery according to claim 8, characterized in that: In the external pressure assistance, the external pressure is 0.1 MPa to 50 MPa; In the temperature assistance, the temperature is -30 to 90°C; In the electrochemical charge and discharge cycle assistance, the electrochemical charge and discharge cycle is 0.01 to 0.1 C current.
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises a solid or semi-solid electrolyte, a negative electrode sheet, a composite positive electrode and the in-situ formation agent according to claim 1; The solid or semi-solid electrolyte includes Li6PS5Cl, Li 6.4 LqCy 1.4 Ta 0.6 O 12 , a composite of one or more of LiAlOCl4, LiNbOCl4, Li3InCl6 and a PEO-based polymer; The raw materials for preparing the negative electrode sheet include at least one of lithium metal, lithium-containing compounds, silicon, silicon-containing compounds, carbon and carbon-containing compounds; the composite positive electrode is prepared by uniformly mixing electrolyte materials, positive electrode active materials and conductive carbon materials in a mass ratio of (30% to 50%): (70% to 50%): 1%; Wherein, the electrolyte material includes the in-situ formation agent or the solid or semi-solid electrolyte.
11. The all-solid-state battery according to claim 10, characterized in that: The positive electrode active material includes CF a , sulfur, sulfur-containing compounds, lithium iron phosphate, lithium-rich positive electrode materials, LiCoO2, and LiNi x Co y Mn 1-x-y O2, where 0.5 < a < 1.3, 0 < x < 1, 0 < y < 1, and x + y < 1; The thickness of the solid or semi-solid electrolyte is 0.03-0.04 mm, the thickness of the negative electrode sheet is 0.02-4 mm, the thickness of the composite positive electrode is 0.01-0.02 mm, and the thickness of the in-situ formation agent is 0.005-0.04 mm.
12. A sodium ion battery in-situ formation agent, characterized in that: The chemical formula of the sodium ion battery in-situ formation agent is Na a M b N c X d ; Wherein, M and N are each independently selected from at least one of Y, La, Ta, Zr, P, Ti, Hf and Al; X is selected from at least one of F, Cl, Br, I, O and S; a is 0~4; b is 0~4; c is 0~4; d is 3~12.
13. Use of a sodium ion battery in-situ formation agent as claimed in claim 12 in the preparation of a sodium symmetric battery or a sodium all-solid-state battery.
Citation Information
Patent Citations
Amorphous halide solid electrolyte, preparation and application in all-solid-state battery
CN113258130A
Solid electrolyte material, preparation method and application
CN116315048A
Multi-element doped halide solid electrolyte material as well as preparation method and application thereof
CN117936881A
Sodium ion halide solid electrolyte, preparation method and all-solid-state sodium ion battery
CN118016986A
Preparation method of oxygen composite halide solid electrolyte
CN118117155A